Association between the victim’s menstrual cycle phase and genital injuries following sexual assault - Vu, Annie; Moaddel, Victoria; Emmerich, Bradley; Rossman, Linda; Bach, Jennifer; Seamon, Jason; Barnes, Mariah; Ouellette, Lindsey; Jones, Jeffrey (Clinical Journal of Obstetrics and Gynecology, 2023)
Background: It is unknown what effect the menstrual cycle can have on the susceptibility to trauma following sexual assault. Objectives: To compare the incidence of genital injuries following sexual assault in women with relationship to the three phases of the menstrual cycle Methods: The design was a retrospective, cohort analysis set in a community-based nurse examiner program over a five-year study period. Sexual assault victims were between the ages of 13 - 40 years and agreed to a forensic examination. The menstrual cycle was divided into three phases: follicular, luteal and menses phase. The primary outcomes were the frequency and type of genital injuries documented in relation to the different phases of the menstrual cycle. Results: Case files of 1376 cases of sexual assault were reviewed; 682 (49.6%) met the inclusion criteria. A total of 220 victims (32.3%) were in the follicular phase, 361 (52.9%) were in the luteal phase and 101 (14.8%) were in the menses phase. The three groups were comparable in terms of demographics, assault characteristics, and overall frequency of non-genital injuries. Assault victims in the follicular phase of the menstrual cycle had significantly more documented genital injuries (72.3%; 95% CI 66.4 - 78.2) compared to the luteal phase (64.0%; 95% CI 59.0 - 68.9) and the menses phase (58.4%; 95% CI 48.8 - 68.0). Conclusion: Forensic examiners documented more genital injuries in the follicular phase of the menstrual cycle. Sex hormones may have confounding effects through influences on vaginal epithelial and mucosal integrity.